Revision of Severe Nasal Trauma - Frodel, John L. (Facial Plastic Surgery, 2012)
Facial trauma commonly includes injury to the nose and perinasal area. In this review, we will focus on the sequelae of severe nasal trauma and provide examples of correction of the severely deviated nose, the severely collapsed nose, and revision of a traumatic deformity after prior rhinoplasty. We will then discuss coexistent deformities of perinasal regions in addition to functional and posttraumatic nasal correction, including posttraumatic periorbital deformities.
Keywords: nasal trauma; nasal deformity; rhinoplasty